E-Procurement as a Pillar of Good Governance: A Literature Review of Fraud Prevention Efforts in the Public Sector - Marisa Triana Mazta; Rindu Rika Gamayuni; Tri Joko Prasetyo (ROE: Research of Economics and Business, 2025)
This study aims to examine the role of e-Procurement as a pillar of Good Governance in preventing fraud within public sector goods and services procurement in Indonesia. The research employs a literature review approach by analyzing ten reputable national and international journal articles that investigate the relationship between e-Procurement implementation, fraud prevention, and the application of Good Governance principles. The findings consistently reveal that e-Procurement has a significant effect on fraud prevention through enhanced transparency, accountability, and efficiency in the procurement process. Several studies also highlight that its effectiveness depends on key determinants such as human resource competence, internal control systems, regulatory support, and organizational commitment to integrity. Moreover, social factors and community participation serve as complementary mechanisms that strengthen public oversight and transparency. Overall, this study concludes that e-Procurement functions not merely as a technological tool but as a governance instrument that reinforces integrity, accountability, and public trust in achieving clean and transparent government administration. The novelty of this article lies in its integrative synthesis that conceptualizes e-Procurement as both a technological innovation and a governance mechanism, bridging the gap between digital transformation and fraud prevention in the Indonesian public sector.